(untitled) (Journal of history, 2019)
In this article we talk about the main types of family rites of kazakhs and the etiquettes of the Kazakh peoplе. The article contains data on ancient and modern etiquettes and the custom of our people. Considering modern ethical culture of Kazakhs, it is possible to say that there are both new and traditional lines. In general traditional culture of Kazakhs including the etiquette investigated by us, is gradually transformed under the influence of modernization processes in the direction of unification and simplification. as well as we answer such questions as «why it is necessary to observe etiquette norms», «what is the difference between modern and ancient etiquette norms», «what custom is used in what circumstances». As a result, we learned many interesting things about the peculiarities of our custom and got a comparison of the etiquette norms of all times.